Bibliometric analysis of oncolytic virus research, 2000 to 2018. Issue 35 (August 2019) - Zou, Yidi; Luo, Yong; Zhang, Jun; Xia, Ningshao; Tan, Guowei; Huang, Chenghao
Abstract: Background: Accumulating evidence in the last decade has pointed to the effectiveness of oncolytic virus in the treatment of a variety of cancer types in preclinical or clinical studies, showing high potency and low toxicity compared to conventional treatments. To track this research trend and highlight future directions, we conducted a bibliometric analysis of oncolytic virus research to date. Methods: Relevant studies were obtained from the Web of Science Core Collection between January 2000 and December 2018. Data were collected in terms of the number of publications, country, journal of publication, journal scope, author, and keywords or topics. Analysis and visual representation of the data were performed with CiteSpace V. Results: The trend in publications related to oncolytic virus showed a dramatic increase, from 10 publications in 2000 to 199 publications in 2018. The United States clearly dominates this field (981 publications, 52.770%), followed by Canada (244, 13.125%) and China (205, 11.027%). The top 15 academic journals account for over one third of the total publications on oncolytic virus research (724, 38.95%). Most of the related papers were published in journals with a focus on biology, medicine, immunology, medicine, molecular biology, and clinical perspectives, as represented by the dual-map overlay. The most highly cited papers were published in journals in the fields of nursing, molecular biology, general biology, genetics, health, and medicine. Over 1300 institutions have focused their attention on oncolytic virus research to date, and cooperation among mainstream institutions is common. Conclusion: The global field of oncolytic virus research has expanded at a rapid pace from 2000 to 2018. There is no doubt that North America currently has the most powerful impact on the field with respect to both productivity and contribution. However, European and some East Asian institutions are also prominent in this field. Overall, this bibliometric study identifies the top 4 hotspots in oncolytic virus research: T-cells, vaccinia virus, dendritic cells, and apoptosis. Thus, further research focuses on these topics may be more helpful to promote the clinical translation of this treatment strategy to bring a benefit to cancer patients in the near future. Abstract : Supplemental Digital Content is available in the text